Stakeholder co-design of sustainable urban pest management strategies - Elizabeth C. Lowe; Nathan J. Butterworth; Alexander Austin; Cameron Webb; Tanya Latty (Ambio, 2026)
The high levels of broad-spectrum insecticides used to manage invertebrates in many cities around the world has significant environmental and health impacts. Integrated pest management (IPM) is a framework for sustainable pest control practice, but uptake of IPM remains low in most cities. We used participatory action research with pest management industry stakeholders (practitioners, industry representatives, researchers and government employees) to identify key issues in urban pest management in Australia, set priorities for change and discuss collaborative solutions. Via an online survey and a face-to-face workshop, the participants identified the key themes of education and training, public awareness, environmental impacts and lack of IPM uptake. We present a summary of the top eight issues, the priorities identified for each one and the co-designed recommended actions that different stakeholders can take to support a shift towards more sustainable pest management practices in urban settings.

Vascular dysfunction occurs prior to the onset of amyloid pathology and Aβ plaque deposits colocalize with endothelial cells in the hippocampus of female APPswe/PSEN1dE9 mice - Emily W. Waigi; Laena Pernomian; Alexia M. Crockett; Tiago J. Costa; Paul Townsend; R. Clinton Webb; Joseph A. McQuail; Cameron G. McCarthy; Fiona Hollis; Camilla F. Wenceslau (GeroScience, 2024)
Increasing evidence shows that cardiovascular diseases (CVDs) are associated with an increased risk of cognitive impairment and Alzheimer’s diseases (AD). It is unknown whether systemic vascular dysfunction occurs prior to the development of AD, if this occurs in a sex-dependent manner, and whether endothelial cells play a role in the deposition of amyloid beta (Aβ) peptides. We hypothesized that vascular dysfunction occurs prior to the onset of amyloid pathology, thus escalating its progression. Furthermore, endothelial cells from female mice will present with an exacerbated formation of Aβ peptides due to an exacerbated pressure pulsatility. To test this hypothesis, we used a double transgenic mouse model of early-onset AD (APPswe/PSEN1dE9). We evaluated hippocampus-dependent recognition memory and the cardiovascular function by echocardiography and direct measurements of blood pressure through carotid artery catheterization. Vascular function was evaluated in resistance arteries, morphometric parameters in the aortas, and immunofluorescence in the hippocampus and aortas. We observed that endothelial dysfunction occurred prior to the onset of amyloid pathology irrespective of sex. However, during the onset of amyloid pathology, only female APP/PS1 mice had vascular stiffness in the aorta. There was elevated Aβ deposition which colocalized with endothelial cells in the hippocampus from female APP/PS1 mice. Overall, these data showed that vascular abnormalities may be an early marker, and potential mediator of AD, but exacerbated aortic stiffness and pressure pulsatility after the onset of amyloid pathology may be associated with a greater burden of Aβ formation in hippocampal endothelial cells from female but not male APP/PS1 mice. Graphical Abstract

Soluble and insoluble protein aggregates, endoplasmic reticulum stress, and vascular dysfunction in Alzheimer’s disease and cardiovascular diseases - Emily W. Waigi; R. Clinton Webb; Melissa A. Moss; Mark J. Uline; Cameron G. McCarthy; Camilla Ferreira Wenceslau (GeroScience, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Mosquitoes associated with an urban estuary and implications for the management of pest and public health risks in Sydney, Australia - Bassam Sahar; Isabel Hess; Jayne Hanford; Cameron Webb (Wetlands Ecology and Management, 2021)

St. Helena: An Important Reproductive Habitat for Whale Sharks (Rhincodon typus) in the Central South Atlantic - Cameron T. Perry; Elizabeth Clingham; D. Harry Webb; Rafael de la Parra; Simon J. Pierce; Annalea Beard; LeeAnn Henry; Beth Taylor; Kenickie Andrews; Rhys Hobbs; Gonzalo Araujo; Alistair D. M. Dove (Frontiers in Marine Science, 2020)

Habitat Traits Associated with Mosquito Risk and Aquatic Diversity in Urban Wetlands - Jayne K. Hanford; Cameron E. Webb; Dieter F. Hochuli (Wetlands, 2019)

Engaging urban stakeholders in the sustainable management of arthropod pests - Elizabeth C. Lowe; Tanya Latty; Cameron E. Webb; Mary E. A. Whitehouse; Manu E. Saunders (Journal of Pest Science, 2019)

Discovery of new orbiviruses and totivirus from Anopheles mosquitoes in Eastern Australia - Agathe M. G. Colmant; Kayvan Etebari; Cameron E. Webb; Scott A. Ritchie; Cassie C. Jansen; Andrew F. van den Hurk; Helle Bielefeldt-Ohmann; Jody Hobson-Peters; Sassan Asgari; Roy A. Hall (Archives of Virology, 2017)

Surrounding land use significantly influences adult mosquito abundance and species richness in urban mangroves - Suzi B. Claflin; Cameron E. Webb (Wetlands Ecology and Management, 2017)

The fungal cultivar of leaf‐cutter ants produces specific enzymes in response to different plant substrates - Lily Khadempour; Kristin E. Burnum‐Johnson; Erin S. Baker; Carrie D. Nicora; Bobbie‐Jo M. Webb‐Robertson; Richard A. White; Matthew E. Monroe; Eric L. Huang; Richard D. Smith; Cameron R. Currie (Molecular Ecology, 2016)
Herbivores use symbiotic microbes to help derive energy and nutrients from plant material. Leaf‐cutter ants are a paradigmatic example, cultivating their mutualistic fungus Leucoagaricus gongylophorus on plant biomass that workers forage from a diverse collection of plant species. Here, we investigate the metabolic flexibility of the ants’ fungal cultivar for utilizing different plant biomass. Using feeding experiments and a novel approach in metaproteomics, we examine the enzymatic response of L. gongylophorus to leaves, flowers, oats or a mixture of all three. Across all treatments, our analysis identified and quantified 1766 different fungal proteins, including 161 putative biomass‐degrading enzymes. We found significant differences in the protein profiles in the fungus gardens of subcolonies fed different plant substrates. When provided with leaves or flowers, which contain the majority of their energy as recalcitrant plant polymers, the fungus gardens produced more proteins predicted to break down cellulose: endoglucanase, exoglucanase and β‐glucosidase. Further, the complete metaproteomes for the leaves and flowers treatments were very similar, while the mixed substrate treatment closely resembled the treatment with oats alone. This indicates that when provided a mixture of plant substrates, fungus gardens preferentially break down the simpler, more digestible substrates. This flexible, substrate‐specific enzymatic response of the fungal cultivar allows leaf‐cutter ants to derive energy from a wide range of substrates, which likely contributes to their ability to be dominant generalist herbivores.

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)